Reflections on Neurofeminism and Intersectionality Using Insights From Psychology - Duchesne, Annie; Kaiser Trujillo, Anelis (Frontiers in Human Neuroscience, 2021)
Intersectionality contends that sex/gender is constituted of and with other social categories, and that the social structures giving rise to inequality should be addressed in research. This is a powerful and important perspective from which to investigate the processes and consequences of social group memberships, one which has been overlooked by most neuroscientific research. In particular, neurofeminism, a field of critical neuroscience that challenges neuroscientific assumptions, methods and interpretations of data that reinforce sexism, has ignored intersectionality to date. In contrast, research in the field of psychology has been engaging with intersectionality for more than a decade. In reflecting on how intersectionality has advanced feminist research in psychology, this paper provides a critical analysis of potential novel research avenues for neurofeminism. We identify three main research themes guided by intersectionality. The first theme involves research centred on understanding the socio-structural causes of health inequalities experienced by individuals with intersecting marginalized social identities; the second concerns research addressing the psychological processing of social group memberships that underlies the enactment of systemic discriminatory practices; and the third theme comprises intersectionality research that aims to challenge psychological epistemology. Drawing parallels between the fields of psychology and neuroscience, we explore the potential benefits and risks of advancing an intersectionality-informed neurofeminism.